Investigations on small molecule inhibitors targeting the histone H3K4 tri-methyllysine binding PHD-finger of JmjC histone demethylases - Bhushan, Bhaskar (Bioorg Med Chem, 2018)
Plant homeodomain (PHD) containing proteins are important epigenetic regulators and are of interest as potential drug targets. Inspired by the amiodarone derivatives reported to inhibit the PHD finger 3 of KDM5A (KDM5A(PHD3)), a set of compounds were synthesised. Amiodarone and its derivatives were observed to weakly disrupt the interactions of a histone H3K4me3 peptide with KDM5A(PHD3). Selected amiodarone derivatives inhibited catalysis of KDM5A, but in a PHD-finger independent manner. Amiodarone derivatives also bind to H3K4me3-binding PHD-fingers from the KDM7 subfamily. Further work is required to develop potent and selective PHD finger inhibitors.